(untitled) (Annals of Medical Research, 2023)
Aim: Scintigraphy is an important nuclear medicine imaging method that is used for detecting various pathological conditions and provides very useful functional information for clinicians. YouTube is the website that patients commonly use to get any information. This study aims to examine the scintigraphy related videos on YouTube. Materials and Methods: This study was conducted in June 2023. Videos were accessed using the keyword "scintigraphy" on YouTube. These videos were evaluated using the Journal of the American Medical Association (JAMA) benchmarks, global quality scale (GQS) and the DISCERN scale. Results: All videos accessed using the keyword "scintigraphy" on YouTube were reviewed. The study includes twenty-six of the examined videos. The source of most of the videos was non-physician. Physician-sourced videos had higher Discern scores, JAMA scores, and the number of likes and comments. However, those who were followed the most and had the highest view ratio were of non-physician-sourced. Physician-sourced videos were of higher quality than non-physician-sourced videos in the quality review (p:0.015). Furthermore, the GQS score, DISCERN score and JAMA score were positively correlated. Conclusion: Patients and caregivers can use YouTube for any disease and treatment. For this reason, official videos should be uploaded to the YouTube platform so that patients can access qualified, complete and accurate content. The URLs of these videos can be added to the patient information forms as QR codes.